Evaluation of the Vitek MS and the MALDI Biotyper systems for the identification of less commonly isolated but clinically relevant anaerobes and facultative anaerobes. (December 2018) - Ferrand, Janina; Bonnet, Isabelle; Alauzet, Corentine; Lozniewski, Alain
Abstract: The Vitek MS and MALDI Biotyper systems were evaluated for the identification of 221 strains belonging to less commonly isolated anaerobes and facultative anaerobes. Identifications were performed using direct deposit (DD), on-target extraction (FA) and full extraction (EXT). After DD, 29.9% and 34.3% of Gram-positive isolates ( n  = 137) as well as 36.9% and 58.3% of Gram-negative isolates ( n  = 84) were identified at the species-level with the Vitek-MS and the Biotyper system, respectively. The rates of correct species identification with the Biotyper system were significantly increased after extraction for Gram-positive isolates (FA: 75.2%, EXT: 78.1%) and Gram-negative isolates (FA: 72.6%, EXT: 78.6%). Extraction permitted to achieve higher correct species identification rates only for Gram-positive isolates (FA: 35.8%, EXT: 36.5%) with the Vitek MS. Thus, the accuracy of both systems needs to be further increased by expanding the databases. In the meantime, we recommend using a preliminary extraction step to obtain reliable results at least for the identification of Gram positive anaerobic bacteria with both systems. Highlights: An increasing number of anaerobic bacteria belonging to new genera and species are recognized as human pathogens. The Vitek MS and the MALDI Biotyper were evaluated for the identification of rarely encountered anaerobic pathogens. For Gram-positive bacteria, higher species identification rates were achieved after extraction with both systems. The accuracy of both systems needs to be further increased by expanding the databases.